Biomechanical comparison of locking femoral neck plate versus cannulated screws with or without a medial buttress plate in Pauwels type 3 femoral neck fractures - Yilmaz Onder; Tugrul Bulut; Osman Nuri Eroglu; Samet Ciklacandir; Yalcin Isler (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate whether the locking femoral neck plate (LFNP) can be an alternative fixation method to the cannulated screws with a medial buttress plate. For this purpose, we compared biomechanically the LFNP and cannulated screws with or without a medial buttress plate in Pauwels type 3 femoral neck fractures.